Hospital based study on etiopathogenesis and treatment of otomycosis: ethnic Kashmiri population - Sumbria, Deepshikha; Yousuf, Aamir; Ahmad, Rauf (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Otomycosis is the fungal infection of the external ear with bothersome symptoms. The target of the study was to verify the frequency and identification of fungi responsible for the otomycosis and to give the most appropriate treatment. The aims and objectives of the study was to study clinical profile, causative fungal organisms of otomycosis, detect in vitro efficacy of various antifungal solutions against the fungi detected and to establish clinical efficacy of various topical antimycotic solutions in otomycosis in Kashmir. Methods: This study was conducted in the Department of ENT, GMC, Srinagar from February 2014 to July 2015. 152 clinically suspected otomycosis patients were subjected to mycological tests including Gram staining, 10% KOH staining, GTT, SDA and CBL stain to identify the organism. Clotrimazole, terbinafine, lulliconazole, sertaconazole and combination of 1% clotrimazole, chloremphenicol, beclomethasone were given randomly in equal number of these patients. Patients were followed for 4 weeks and results of different antifungals were evaluated clinically. Results: Out of 152 patients 61.8% were females and most of the patients belonged to age group of 25-34 yrs.Most of the patients reported in summer season. Otalgia and itching was the most common symptom. Aspergillus was the most common species identified whereas Candida albicans was the most common individual organism isolated. Lulliconazole was most effective drug whereas combination of 1% clotrimazole, chloremphenicol, beclomethasone was least effective. Conclusions: Clinical suspicion of otomycosis is important to prevent unnecessary use of antibiotics. Diagnosis of otomycosis is usually made by clinical findings with pruritis being most common symptom followed by otalgia. In-vitro sensitivity test is of great importance to choose the most active antifungal agents. Patients are advised to avoid removing of ear wax by stiff materials.